2016
DOI: 10.1049/iet-rsn.2015.0046
|View full text |Cite
|
Sign up to set email alerts
|

Non‐coherent pulse compression — aperiodic and periodic waveforms

Abstract: The growing interest in adopting pulse compression waveforms to non-coherent radar and radar-like systems (e.g. lidar) invites this update and review. The authors present different approaches of designing on-off {1, 0} coded envelopes of transmitted waveforms whose returns can be envelope detected and non-coherently processed. Two approaches are discussed for the aperiodic case: (a) Manchester encoding and (b) mismatched reference. For the periodic case, on-off sequences are described, which produce perfect pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…maximising the SNR improvement, so-called coding gain, whilst minimising the hardware overhead and extra measurement time); however, all currently existing code types present fundamental and/or practical limitations. For instance, although codes formed by a single sequence 40,[56][57][58][59][60][61][62]64 are ideal for minimising measurement time and data storage, they either exhibit an imperfect peak-tosidelobes ratio after the decoding 40,56,64 or are periodic/cyclic codes [57][58][59][60][61][62]64 that suffer from impairments induced by signaldependent noise 1 (resulting in a compromised coding gain that has not yet been quantified in literature). As more robust alternatives, distortion-free aperiodic codes constituted by several sequences, such as Golay [41][42][43][44][45][46][47] , Simplex codes [48][49][50][51][52]63 and their derivatives 54,55 , have been mostly used for DOFS.…”
mentioning
confidence: 99%
“…maximising the SNR improvement, so-called coding gain, whilst minimising the hardware overhead and extra measurement time); however, all currently existing code types present fundamental and/or practical limitations. For instance, although codes formed by a single sequence 40,[56][57][58][59][60][61][62]64 are ideal for minimising measurement time and data storage, they either exhibit an imperfect peak-tosidelobes ratio after the decoding 40,56,64 or are periodic/cyclic codes [57][58][59][60][61][62]64 that suffer from impairments induced by signaldependent noise 1 (resulting in a compromised coding gain that has not yet been quantified in literature). As more robust alternatives, distortion-free aperiodic codes constituted by several sequences, such as Golay [41][42][43][44][45][46][47] , Simplex codes [48][49][50][51][52]63 and their derivatives 54,55 , have been mostly used for DOFS.…”
mentioning
confidence: 99%
“…The PACF clearly show that the magnitude of sidelobes other than peak is '1' which is constant. Levanon [13] and Jahangir [14] demonstrated the ideal periodic correlation properties of M-sequences and Legendre sequences by taking the crosscorrelation between the unipolar version {1, 0} of transmitted signal and the bipolar reference signal {±1}. It is shown that this method is advantageous in context of Non-coherent Pulse Compression (NCPC) radar.…”
Section: Sequences With Perfect Periodic Autocorrelationmentioning
confidence: 99%
“…The perfect periodic cross-correlation property is achieved at the cost of high energy loss. The energy efficiency of unipolar M-sequence (N=7) is nearly 57% and such signals are preferred in noncoherent processing [13,14]. For coherent processing, the reference signal must be same as the transmitted signal.…”
Section: Sequences With Perfect Periodic Autocorrelationmentioning
confidence: 99%
“…Noncoherent pulse compression (NCPC) introduced in [7]- [9] employs the on-off keying (OOK) modulation. The OOK transmitted signal suggested for NCPC are based on Manchester coding well-known binary sequences, like Barker or minimum peak sidelobe (MPSL) codes.…”
Section: Related Previous Techniquementioning
confidence: 99%